Effectiveness Of Science Learning Using Guided Experiment Method In Terms Of Scientific Attitudes And Learning Outcomes Of Fourth Grade Elementary School Students - Nisa, Santi Khasiatin; Utaminingsih, Sri; Rondli, Wawan Shokib (Advances In Social Humanities Research, 2025)
This study evaluates the effectiveness of the guided experimental method on improving learning outcomes and scientific attitudes among fourth-grade students in seven elementary schools in Jakenan Subdistrict, Pati District. Employing a quantitative experimental design, this study compares the performance of students receiving instruction through the guided experimental method (experimental class) with those following a conventional approach (control class), including a sample from SD Tambahmulyo 01 (experimental class) and eight other schools as control classes. Rigorous validity prerequisite tests were conducted. The Pre-test Normality test for the experimental group showed a significance value of 0.902 and for the control group 0.278, both indicating a normal data distribution. The Post-test yielded a significance value of 0.063 for the experiment and 0.356 for the control, indicating data normality. The Homogeneity test produced a Levene's statistic based on the mean of 0.062 with a significance value of 0.805, affirming the homogeneity of variances across groups. Conclusion Based on the met prerequisites, further analysis shows that the guided experimental method significantly improves students' scientific attitudes, proving its effectiveness not only in enhancing learning outcomes but also in promoting a positive scientific attitude.